The Influence of Perceived Stress and Emotional Intelligence on Suicidal Ideation in Early Adulthood - Franyanti, Alvira; Sovitriana, Rilla (Dinasti Health and Pharmacy Science, 2023)
Suicide is a mental health condition that has received attention in many countries over the years. Suicide is a mental health problem that increases the overall burden of mental and physical illness, especially in young people. This study used 97 respondents who were sampled in the study. The sampling technique used in this study was purposive sampling. Data collection methods using the scale of perceived stress, emotional intelligence, and suicidal ideation with a Likert scale model. Based on the results of partial hypothesis testing, it shows that there is an influence with a positive direction between perceived stress on suicidal ideation in early adulthood. The results of hypothesis testing partially show that there is an influence with a negative direction between emotional intelligence on suicidal ideation of early adults in Jabodetabek. The results of simultaneous hypothesis testing show that there is a significant influence between perceived stress and emotional intelligence on suicidal ideation in early adulthood.